Exploring the involvement of ferroptosis-associated genes and pathways in mesenchymal stem cell aging through bioinformatics analysis - Mavaddatiyan, Laleh; Khamineh, Yasaman; Taghiyar, Leila; Talkhabi, Mahmood (Frontiers in Aging, 2025)
Mesenchymal stem cells (MSCs) exhibit self-renewal and multipotent differentiation capabilities, and play roles in tissue repair and regeneration. However, age-related alterations can impair MSCs functions, potentially contributing to accelerated aging processes. Ferroptosis, a regulated form of cell death involving iron-mediated lipid peroxidation, is implicated in age-related diseases, although its specific role in MSCs aging remains unclear. Herein, the GSE68374 dataset was analyzed to obtain ferroptosis-related differentially expressed genes (FRDEGs). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed, and potential drugs targeting FRDEGs were predicted. Protein-protein interaction (PPI) analysis was conducted and hub genes were identified, which were validated using two independent datasets. Furthermore, an integrated regulatory network of kinases, transcription factors (TFs), and microRNAs was constructed. A total of 131 FRDEGs were screened, which were involved in cellular responses to starvation, oxidative stress, lipid metabolism, cellular senescence, ferroptosis, and cancer pathways. Among twenty hub genes, eight key FRDEGs, including activating transcription factor 3 (ATF3), Enhancer of zeste homolog 2 (EZH2), synuclein alpha (SNCA), prostaglandin-endoperoxide synthase 2 (PTGS2), NADPH oxidase 4 (NOX4), cyclin-dependent kinase inhibitor 2A (CDKN2A), sequestosome 1 (SQSTM1), and interleukin 6 (IL6), were similarly regulated across external datasets, and the expression of these genes was also confirmed by qRT-PCR. These findings highlight the pivotal role of these genes in MSCs aging and ferroptosis, suggesting that targeting them could enhance MSCs regenerative capacity and mitigate the progression of aging-related alterations in MSCs.